MENINGKATKAN KREATIVITAS ANAK DENGAN ADHD MELALUI LITERASI - Andi Purnawan Putra (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2018)
Reliable and qualified Human Resources (HR) can be realized through improving the quality of education where this can be achieved through literate HR. High literacy skills will produce creativity in the form of new ideas or ideas that are useful for solving problems. Children with concentration disorders such as ADHD need learning stimulation that can help increase creativity through literacy. So it is necessary to develop literacy models in order to increase the creativity of children with ADHD to be more optimal. Literacy models that can be developed include: 1) Multisensory literacy models; 2) the play therapy model and 3) the personal-social guidance model. The right literacy model will help children minimize and reduce the symptoms of ADHD which in turn can focus on developing interests and talents to be more creative.